1986
DOI: 10.1128/mcb.6.8.2944
|View full text |Cite
|
Sign up to set email alerts
|

Azacytidine-induced reactivation of a DNA repair gene in Chinese hamster ovary cells.

Abstract: Six X-ray-sensitive (xrs) strains of the CHO-Kl cell line were shown to revert at a very high frequency after treatment with 5-azacytidine. This suggested that there was a methylated xrs+ gene in these strains which was structurally intact, but not expressed. The xrs strains did not complement one another, and the locus was autosomally located. In view of the frequency of their isolation and their somewhat different phenotypes, we propose that the xrs strains are mutants derived from an active wild-type gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 48 publications
(55 reference statements)
1
35
0
Order By: Relevance
“…2C) When xrs5 cells are reverted to X-ray resistance with azacytidine, DEB activity is also restored. Treatment with azacytidine will induce xrs5 cells to revert to X-ray resistance at a frequency of about 1% (20). Azacytidine acts as a competitive inhibitor of methyltransferase to demethylate previously methylated, and therefore silenced, genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C) When xrs5 cells are reverted to X-ray resistance with azacytidine, DEB activity is also restored. Treatment with azacytidine will induce xrs5 cells to revert to X-ray resistance at a frequency of about 1% (20). Azacytidine acts as a competitive inhibitor of methyltransferase to demethylate previously methylated, and therefore silenced, genes.…”
Section: Resultsmentioning
confidence: 99%
“…Binding activity to the DNA probe f148 (or f320) was measured by a gel electrophoretic mobility shift assay described previously (7,8,17,35 Azacytidine-induced revertants of xrs5. Azacytidine was used to revert xrs5 cells to X-ray resistance as described previously (20). Briefly, 10' cells were seeded into a 25-cm2 flask, allowed to attach, and then grown for 15 h in medium containing 3 ,ug of freshly dissolved 5-azacytidine (Sigma, St. Louis, Mo.)…”
Section: Methodsmentioning
confidence: 99%
“…Siminovitch (41) has suggested that a substantial part of the genome in Chinese hamster cell lines is effectively haploid so that many genes are represented by only one functional allele. Functional hemizygosity can arise from the silencing of genes by methylation, and group 5 hamster cell mutants might have two alleles of the XRCC5 gene, with one allele inactivated by mutation and another wild-type allele silenced by methylation (22). RNAs derived from revertants XR-V15B-Rev1 and XR-V15B-Rev2 harbor both wild-type and deleted Ku86 sequences.…”
Section: Discussionmentioning
confidence: 99%
“…25 Similarly, besides being a G1 regulator, p16 has a very important role in cellular senescence. 26 This may be one of the reasons attributed to its independent effect to radiotherapy response.…”
Section: Adenoviral P16mentioning
confidence: 99%